STUDY OF VARIATIONS IN GROOVED PRESS ROLLER LOADING ON THE TENSILE STRENGTH OF UMBRELLA GRASS FIBERS - Anom Palmatira, Dismas; Murdiyanto, Danang; Cristanto Putra Mbulu, Bernadus (Mechanical, Energy and Material (METAL), 2024)
Composite materials have better material properties than ordinary materials. Based on current developments, the author participates in the development of composite materials by making a fiber from umbrella grass which is used to make composite materials. The author uses a grooved roller press to make umbrella grass fibers, using various loadings of 35kg, 40kg and 45kg, umbrella grass that has been rolled then looks at the structure of the fiber whether there is damage or fracture then every loading 3 fiber samples are taken and tested to obtain the strength value maximum pull. After the test data is obtained, calculations are carried out to obtain the maximum tensile strength value of each sample. The results obtained from each fiber with the highest tensile strength are loading of 35 kg with a tensile strength of 61.13478261MPa with a well-formed fiber structure, defects or fractures occur, then loading of 40 kg with a tensile strength of 55.90645161MPa with a well-formed fiber structure without Defects occurred and the final loading was 45 kg with a tensile strength of 28.02857143 MPa with the fiber structure formed where there were broken or defective parts of the fiber. Based on the research that has been done, umbrella grass fiber which has the highest tensile strength value and also has good fiber without damage is fiber at a loading of 35 kg.